STUDI EFEK SAMPING ANTITUBERKULOSIS PADA PASIEN RAWAT JALAN DI SALAH SATU RUMAH SAKIT DI GARUT - Fadhilla, Genialita; Fatimah P.H, Sitti; Rahma, Asilia (Acta Pharmaceutica Indonesia, 2025)
Tuberculosis remains a global health problem with high incidence and mortality rates, 724,309 people infected with tuberculosis. One of the challenges in the treatment of tuberculosis is side effects of antituberculosis (OAT) which can lead to treatment discontinuation and drug resistance. This study aimed to identify the incidence of OAT side effects in outpatient tuberculosis patients at DOTS clinic in one of  hospitals at Garut. This study used a descriptive survey design with a cross-sectional. Data were collected from 31 tuberculosis patients who met the inclusion criteria through interviews and medical records review during May-June 2024. Respondents used fixed dose combination (FDC) therapy (94% ) and  single drug formulation(6%). OAT side effects are divided into mild and severe effects. The mild side effects most often experienced by respondents were redish urine (94%), flu-like symptoms (81%), and joint pain (77%). Meanwhile, the most common severe side effect experienced by respondents was visual (23%). Side effects are managed by administering symptomatic drugs such as antiemetics, analgesics, antipyretics, and vitamin B6. Intensive monitoring and appropriate management of side effects are essential to improve treatment adherence, prevent drug resistance, and reduce morbidity and mortality from tuberculosis.